A new dark-winged fungus gnat genus, Linana Shah & Huang gen. nov. (Diptera: Sciaridae), from China, with descriptions of two new species - Shah, Bismillah; Shao, Yisa; Zhu, Yi; Huang, Junhao (Zootaxa, 2026)
A new genus of dark-winged fungus gnats, Linana Shah & Huang gen. nov. is described from China, with two newly described species: Linana primaria Shah & Huang gen. et sp. nov. as a type species, and Linana confusa Shah & Huang gen. et sp. nov. Morphologically, this genus combines the characters of different clades, by having long and bottleneck-shaped flagellomeres, an undifferentiated tibial organ and non-setose posterior wing veins, but unique male genitalia. DNA barcode data (COI) further support its genetic distinctiveness.